Glocalization as the dominant trend in the development of socio-political being: conflict models and constructs - Schelkunov, Mikhail Dmitrievich; Volchkova, Olga Olegovna; Krasnov, Anton Sergeevich (Linguistics and Culture Review, 2021)
Being a complex dialectical interaction process for differently directed social centrifugal and centripetal movements, glocalization leads to a significant transformation of political being and consciousness (Chumakov, 2016). Being a natural reaction to the developing unification narrative, the localization and differentiation tendencies, on the other hand, become a causal basis of the struggle for overcoming differences. Both trends symbolize, within their frameworks, the basic values of each narrative and create their political mythologies, each of which has an impact on the collective stratum of consciousness and, as a consequence, on a certain model of socio-political behavior of individuals. Political "myths of global unity" lead the core constructions of political and social being - the nation and the state - to a decrease in their authority and legitimacy level; at the same time, the "mythology of difference", while preserving the dominant political values, reorients them to local manifestations, also losing their connection with the central elements of the political matter. Thus, special conflictual forms of development are formed in contemporary society and are conditioned by both real objective preconditions and artificially generated constructs. Socio-political being, therefore, is in a state of dialectical equilibrium and develops within the conflict paradigm.